Forensic Monitoring Project Report: Kula Exhumations Republika Srpska Commission on Missing and Tracing - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Kennedy, Brenda On 8 May 1998 the Republoka Srpska Commission on Missing and Tracing exhumed the remains of five individuals from a cemetery in the town of Kula. Place of Exhumation: Kula Date of Exhumation: 8 May 1998 Minimum Number of Exhumed Individuals: 005